CONNOTATIVE MEANINGS OF ELISION AND SYNCOPE IN ENGLISH AND UZBEK LANGUAGES - Fayzulloyevna, Norova Mavluda; Аskarovich Haydarov Аnvar (International Journal of Psychosocial Rehabilitation, 2020)
The article is dedicated to the phonostylistic features of one of phonetic changes elision in English and Uzbek languages which occur in pronunciation. The connotative meanings conveyed with the omission of sound or syllables in the verbal root-stems of the compared languages are shown on the basis of wellgrounded examples. The phonopragmatic aspects of the literary speech of elision are thoroughly analyzed and studied. The connotative meanings expressed in the case of syncope are also explained on the basis of evincive examples taken from English and Uzbek languages. Syncopic words and their making up the great number in English language, their providing poetic meter specific for rhythmic tone in the artistic image and its creating a sense of artistic impressionability in the reader are conceived in the article.